Development of a Social Science curriculum Using Social Media Applications to Enhance Global Awareness and Digital Citizenship Skills in Elementary School Students - Tapung, Marianus (Technium Social Sciences Journal, 2025)
This research aims to develop social media-based social science learning at an elementary school in Nampong Manggarai to increase students' global awareness and digital citizenship skills. The study involved grade five students as research subjects, utilizing the modified Research and Development (R&D) method of the Borg & Gall model, which is divided into seven stages. Data is collected through observation, interviews, questionnaires, and documentation. The results showed that the developed learning design received positive validation from experts with an average score of 4.0 out of a scale of 5.0. The implementation of learning showed a significant improvement in several aspects: the active participation rate of students reached 85%, global awareness increased by 27.7%, and digital citizenship skills increased by 29.3%. A wide-scale trial of 98 students confirmed the effectiveness of the design with consistent improvements in global awareness (25.7%) and digital citizenship skills (27.2%). The user satisfaction rate reaches 92% for teachers and 90% for students. This research produces a social media-based social science learning design that effectively develops 21st-century competencies, supports the transformation of the educational paradigm from a traditional knowledge transmission model to technology-based transformative learning, and prepares students to become competent and responsible digital citizens.